Advances in Neuroscience and the Biological and Toxin Weapons Convention. (15th September 2010) - Dando, Malcolm
Abstract : This paper investigates the potential threat to the prohibition of the hostile misuse of the life sciences embodied in the Biological and Toxin Weapons Convention from the rapid advances in the field of neuroscience. The paper describes how the implications of advances in science and technology are considered at the Five Year Review Conferences of the Convention and how State Parties have developed their appreciations since the First Review Conference in 1980. The ongoing advances in neurosciences are then assessed and their implications for the Convention examined. It is concluded that State Parties should consider a much more regular and systematic review system for such relevant advances in science and technology when they meet at the Seventh Review Conference in late 2011, and that neuroscientists should be much more informed and engaged in these processes of protecting their work from malign misuse.